The IPSS-R has prognostic impact in untreated patients with MDS del(5q). (September 2018) - Kaivers, J.; Lauseker, M.; Hildebrandt, B.; Fenaux, P.; Pfeilstöcker, M.; Valent, P.; Platzbecker, U.; Latagliata, R.; Oliva, E.N.; Xicoy, B.; Götze, K.; Ganster, C.; et al.
Highlights: The IPSS-R is validated as a prognostic tool for patients with MDS and del(5q). Isolated del(5q) plus one non-chromosome 7 aberration deteriorates the prognosis. Changes in chromosome 7 in the context of del(5q) lead to a poor prognosis. Abstract: The IPSS-R proved to be a powerful tool for the assessment of prognosis in MDS patients. We aimed at a validation of the IPSS-R for patients with MDS harboring deletion (5q) isolated or accompanied by additional aberrations. The study was based on 444 MDS patients from MDS centers in Europe. 67% of the patients were female, median age was 69 years. 43.5% had MDS del(5q), 5.9% were diagnosed with RCUD, 2.0% RARS, 18.4% RCMD, 14.6% RAEB-I and 15.5% RAEB-II. According to the IPSS-R, there were 9.9% very low, 39.6% low, 16.6% intermediate, 12.8% high, 20.9% very high risk patients. For very low risk patients survival was 7.5 years, low 9.0 years, intermediate 6.5 years, high 1.5 years and very high 0.7 years (p < 0.001). For low and intermediate risk, the probability of AML evolution was significantly different (p = 0.03) as well as for high versus very high risk groups (p = 0.002). The IPSS-R proved to be an appropriate prognostic tool for MDS with del(5q).